2022
DOI: 10.1007/s10103-022-03518-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photobiomodulation in reducing pain and improving the quality of life in patients with idiopathic burning mouth syndrome. A systematic review and meta-analysis

Abstract: Burning mouth syndrome is a chronic condition, which is characterised by a burning sensation or pain in the mucosa of the oral cavity. Treatment options include antidepressants, antipsychotics, anticonvulsants, analgesics, hormone replacement therapies and more recently photobiomodulation. This study aims to perform a systematic review with meta-analysis in order to determine the effect of photobiomodulation on pain relief and the oral health-related quality of life associated with this condition. A bibliograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(83 reference statements)
0
6
0
2
Order By: Relevance
“…Ghigiarelliet et al showed short-term effects of whole-body PBM in a sports population, without showing any conclusive change [19]. The effects of local PBM on pain are well known and established [39], and its usefulness has been shown in different conditions such as knee osteoarthritis [40], oral mucositis [41], idiopathic burning mouth syndrome [42], neck disability and chronic neck pain [43], pain and function in tendinopathy [44], myofascial temporomandibular disorder [45], fractures [46], central nervous diseases [47] and even in the microbiome [48]. On the other hand, other studies show that PBM does not decrease pain and disability, specifically in people with non-specific low back pain, although those studies analysed the use of local PBM and not whole-body PBM [49].…”
Section: Discussionmentioning
confidence: 99%
“…Ghigiarelliet et al showed short-term effects of whole-body PBM in a sports population, without showing any conclusive change [19]. The effects of local PBM on pain are well known and established [39], and its usefulness has been shown in different conditions such as knee osteoarthritis [40], oral mucositis [41], idiopathic burning mouth syndrome [42], neck disability and chronic neck pain [43], pain and function in tendinopathy [44], myofascial temporomandibular disorder [45], fractures [46], central nervous diseases [47] and even in the microbiome [48]. On the other hand, other studies show that PBM does not decrease pain and disability, specifically in people with non-specific low back pain, although those studies analysed the use of local PBM and not whole-body PBM [49].…”
Section: Discussionmentioning
confidence: 99%
“…Valenzuela, Pons-Fuster & López-Jornet (2016) e Sugaya et al (2016), embora utilizando outros protocolos, conseguiram resultados semelhantes em seus estudos. Com isso, o laser se configura como uma opção que mais se aproxima de cumprir com os requisitos de um padrão ouro, com efeitos positivos e sem efeitos adversos quando comparado a terapias farmacológicas com efeitos colaterais já bem descritos na literatura, embora, ainda não exista um protocolo terapêutico específico e bem fundamentado no conteúdo científico sobre a SAB (Camolesi et al, 2022;Senra et al, 2021;McMillan et al, 2016).…”
Section: Título Do Artigo Autor E Ano Resultadosunclassified
“…A catuama® tratase de uma terapia farmacológica de tratamento, um fitoterápico cuja literatura não relatou efeitos adversos significativos e que quando contrastado com as outras opções, como por exemplo, benzodiazepínicos e antidepressivos, passa uma maior segurança ao profissional para a prescrição e ao paciente para o seu uso. Além dessa alternativa, e agora tratando-se de terapias não farmacológicas, tem-se a TLBI, que vem cada dia mais ganhando espaço e aplicação na rotina odontológica, um instrumento de fácil manuseio com efeitos positivos bem reconhecidos e fundamentados tanto para o tratamento da SAB quanto para outras condições médico-odontológicas (Camolesi et al, 2022;Matos, et al, 2021;Al-Maweri et al, 2017;Miziara et al, 2015).…”
Section: Título Do Artigo Autor E Ano Resultadosunclassified
“…Although HRQoL and overall well-being have not consistently been primary targets of PBM research, based on a random sample of publications, the authors found evidence that HRQoL is responsive to PBM as part of its biopsychosocial effects. For example, in a systematic review and meta-analysis, Camolesi et al [10] found that there were significant improvements in oral HRQoL in people with burning mouth syndrome. Gautam et al [85] found that physical, emotional, and functional well-being was significantly better in an active PBM treatment group compared to placebo treatment in people receiving chemoradiotherapy for head and neck cancer.…”
Section: Pbm Quality Of Life and Well-beingmentioning
confidence: 99%
“…We suggest that there may be several co-existing phenomena (including mechanisms) that are activated by the application of PBM to a biological system with sentience, and which cannot necessarily be explained by biophysical causes. For example, if one accepts that health-related quality of life (HRQoL) is the individual's overall perceived mental and physical health, PBM must have much more than a molecular analgesic mechanism given that HRQoL has been shown to be positively influenced by PBM, e.g., [10].…”
Section: Introductionmentioning
confidence: 99%